Development of chitosan-α-mangostin loaded nanoparticles as an anticancer agent - Elsaid Ali, Aimen Abdo; Bakhtiar, M. Taher; Mohamed, Farahidah (2011)

(untitled)
α-Mangostin is one of the main active constituents that can be isolated from the stem bark of Garcinia malaccensis (GM) and has been documented to exert different cytotoxic activities against many cancerous cell lines. Due to its non selective distribution into the tissue, this study had attempted to encapsulate the α-mangostin into biodegradable PLGA copolymer using colloidal extraction solvent evaporation method. The polysaccharide Chitosan was incorporated with the loaded nanoparticles to improve their affinity towards lung cancer cells. The resultant nanoparticles were characterized for their size distribution and external morphology by laser diffractometry and scanning electron microscope (SEM), respectively. The concentration of entrapped α-mangostin was determined by HPLC. Our data demonstrated that the encapsulation efficiency for Chitosan-α-mangostin-loaded PLGA nanoparticles (CM-NP) was higher than those without Chitosan (M-NP). The in vitro release from (CM-NP) and (NPM) was carried out in PBS containing 0.1% tween 20 over three weeks. Whereas, in vitro anti-cancer activities of (CM-NP) and (M-NP) were evaluated against lung cancer cell line (A549) and compared to the free α-mangostin. Our data revealed that (CM-NP) showed higher cytotoxic effect compared to (M-NP) and both had lower cytotoxicity than free α-mangostin. In conclusion, PLGA nanoparticles in combination with Chitosan may be used as a promising composite micro-carrier system to deliver α-mangostin to the lung cancer tissue.